HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU IBU DALAM MENGHADAPI MENOPAUSE - Pratiwi Suprianto; Lisda Maria (LPPM STIKes Mitra Adiguna, 2022)
Background: Menopause is an unavoidable stage in the reproductive life of every woman. This stage sometimes makes women unprepared and have negative behavior because of knowledge and attitudes that have not been accepted. The survey in 23 Ilir Palembang village showed that most of the behavior in dealing with menopause was still not good. Objective: to determine the relationship between knowledge and attitudes towards maternal behavior in dealing with menopause at 23 Ilir Health Center Palembang in 2022. Methods: The research design used was observational analytic with a cross-sectional approach. The population taken in this study were all premenopausal women, a total of 887 premenopausal women at the 23 Ilir Health Center with a total sample of 81 people. Data analysis used product moment correlation test followed by simple linear regression. Results: it was found that there was a relationship between knowledge and attitudes with maternal behavior in dealing with menopause at the 23 Ilir Health Center Palembang in 2022 (p value <0.05). The regression equation model on knowledge is Y= 34.628 + 0.314 Knowledge. The regression equation model on attitude is Y= 4.135 + 0.911 attitude. Conclusion: Based on the results of the study, it was found that knowledge had an effect of 9.8% on behavioral variables and attitudes had an influence of 55.0% on behavioral variables. Suggestion: it is recommended to develop a health education model for premenopausal women in increasing knowledge and attitudes so that they can deal with menopausal problems. Keywords: Knowledge, Attitude, Behavior, menopause